Third Ventricular Tumors: A Comprehensive Literature Review - Ahmed, Syed Ijlal (Cureus, 2018)
Third ventricle tumors are uncommon and account for 0.6 - 0.9% of all the brain tumors. Tumors of the third ventricle are classified into primary tumors, such as colloid cysts, choroid plexus papillomas, and ependymomas, or secondary tumors, such as craniopharyngiomas, optic nerve gliomas, pineal tumors, and meningiomas. Third ventricular tumors are uncommon, and their treatment involves significant morbidity and mortality. The colloid cyst has a better surgical outcome and many approaches are available to achieve a complete cure. Choroid plexus papilloma is also a common tumor documented with its treatment majorly based on surgical resection. In addition to multiple treatment options for craniopharyngiomas, surgery is the most preferred treatment option. Ependymomas also have few treatment options, with surgical resection adopted as the first line of treatment.